The Effectiveness of Side Right-in and Crossover Shuffle Training on Improving Agility in Futsal Athletes: A Speed, Agility, and Quickness (SAQ) Approach - Habibi Sutirta; Noor Akhmad (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2025)
This study aims to analyze the effect of two forms of agility ladder drills, namely Side Right-in and Crossover Shuffle, on improving the agility of male futsal athletes from the FIM Squad UNDIKMA. Agility is a crucial physical component in futsal, as it relates to the ability to change direction and respond quickly to game situations. The study employed a quasi-experimental two-group pretest–posttest design, involving 20 athletes. Divided into two training groups. Agility was measured using the Shuttle Run Test. The results showed that both types of training significantly improved agility (p < 0.05), but the Side Right-in group produced a greater average increase than the Crossover Shuffle. Comparisons between groups also showed significant differences, indicating the superiority of Side Right-in training in improving the ability to change direction. In conclusion, agility ladder drills are effective for use in the Speed, Agility, and Quickness (SAQ) program, and Side Right-in training is recommended as a more optimal form of training to improve the agility of futsal athletes. These findings can serve as a basis for trainers in designing more targeted and effective training programs